Biographical Temporalisation(s) in Adult Education - Sabine Schmidt-Lauff (Universidade de Lisboa, 2023)
Time is of central importance for understanding biography. In the biographical narrative, the past and the future are designed and interwoven within an even specific present. In the process of narrating, the subject as self and its identity performance is reconstructed as 'what has become' and as 'what is becoming', and, by this reconstructable too. Each biography thus offers a temporalised construction and representation of identity (Kade, 2011). To elaborate these complex relations, the focus of this paper is to contextualize conceptual, epistemological and methodological aspects of biography and biographical research, such as historical, relational (past-present-future) and indexical references. Working and inquiring ('Bildungs') biographies in (adult) education has a special significance because it can expose constructions of meaning as well as the relational interconnectedness of time, subject and society (Dausien, 2020). The concept of biographical temporalisation(s) would like to pave the way for a differentiated time-related approach to biographies and biographical research in adult education.